2009
DOI: 10.1890/07-1299.1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical methods to correct for observation error in a density‐independent population model

Abstract: Abstract. The problem of observation error in assessing the dynamics of populations over time has received increasing attention of late. Of particular interest has been a densityindependent dynamic model, which allows a trend and is commonly employed in population viability analysis (PVA). Most of the recent work in this area has focused on assessing the impact of the observation error and on finding corrected estimators, primarily under normal models with the observation errors assumed to have a constant vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…As with other studies, we found that measurement error contaminating data sets introduces bias for parameter estimation and model selection (Shenk et al 1998, Staudenmayer and Buonaccorsi 2005, Dennis et al 2006, Buonaccorsi and Staudenmayer 2009). While measurement error can be explicitly incorporated into models for estimation (Bell andWilcox 1993, Staudenmayer andBuonaccorsi 2005), we found that using the simpler approach of fitting ARMA( p,p) models worked reasonably well to estimate the AR coefficients of the model with little excess bias.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As with other studies, we found that measurement error contaminating data sets introduces bias for parameter estimation and model selection (Shenk et al 1998, Staudenmayer and Buonaccorsi 2005, Dennis et al 2006, Buonaccorsi and Staudenmayer 2009). While measurement error can be explicitly incorporated into models for estimation (Bell andWilcox 1993, Staudenmayer andBuonaccorsi 2005), we found that using the simpler approach of fitting ARMA( p,p) models worked reasonably well to estimate the AR coefficients of the model with little excess bias.…”
Section: Discussionsupporting
confidence: 81%
“…Second, we address the issue of measurement error. Measurement error may contaminate time-series data, generating lags in the MA component of a fitted model and causing bias in the coefficient estimates (Shenk et al 1998, Ives et al 2003, Staples 2004, Staudenmayer and Buonaccorsi 2005, Dennis et al 2006, Buonaccorsi and Staudenmayer 2009). Here, we investigate two approaches to incorporating measurement error into ARMA models.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large recent literature concerned with various error terms in population models ( [18,[28][29][30] provide examples). Much of the literature on biases is concerned with decreasing populations, rather than with the growth curves considered here, and it seems that there is little agreement yet on terms and methodology.…”
Section: Biases In Estimationmentioning
confidence: 99%
“…The second of these two data sets is one of the most commonly used examples in the literature on count‐based population viability analysis (e.g., Dennis et al . ; Dennis & Taper ; Morris & Doak ; Lindley ; Buonaccorsi & Staudenmayer ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we re-examine the use of two data sets at the core of the arguments about the population's status, past and present: demographic rate estimates from 1983 to 2001, and relative density estimates from 1973 to the present. The second of these two data sets is one of the most commonly used examples in the literature on count-based population viability analysis (e.g., Dennis et al 1991;Dennis & Taper 1994;Morris & Doak 2002;Lindley 2003;Buonaccorsi & Staudenmayer 2009).…”
Section: Introductionmentioning
confidence: 99%